The Effect of Compensation and Workload on Employee Performance at PT. X Padang City with Job Satisfaction as a Mediating Variable - Nabila Hendrasti; Laura Syahrul; Rahmi Fahmy (Journal of Social Research, 2022)
Background: Based on the production data of PT. X Padang City is known that starting in 2020 there was a decrease in the average number of Production until 2021 and it is also known that from 2019 to 2021 there was no production that reached the target so it was known that employees experienced a decrease in performance. Objective: This study aims to see the effect of compensation and workload on employee performance at PT. X Padang City with job satisfaction as a mediating variable. Method: The determination of samples in this study was carried out by the type of Probability Sampling. The sample in this study was factory employees who worked at PT. X Padang City with 100 employees. The data analysis technique used is path analysis using Smart PLS software. Research hypothesis testing uses T-statistical tests obtained through the bootstrapping process. The hypothesis will be accepted if the T-statistical value > 1.96 and the significance value < 0.05. Results: Results show that employee performance is affected by compensation, workload, and job satisfaction. Work satisfaction mediates the effect of compensation on employee performance job satisfaction does not mediate the effect of of workload on employee performance. Conclusion: PT. X has not provided compensation by employee performance standards and the workload given to employees can be said to be excessive or overloaded with targets to be achieved. This makes employees dissatisfied so that employees become physically tired, psychologically tired, and not excited at work which results in a decrease in performance production at PT X.